Kyrle's Disease in a Patient with Delusions of Parasitosis - Tampa M.; Sârbu Maria Isabela; Matei Clara; Mihăilă Daniela E.; Potecă T. D.; Georgescu Simona-Roxana (Sciendo, 2016)
Acquired perforating disorders are a group of uncommon skin conditions characterized by transepidermal extrusion of altered dermal material, most often associated with diabetes mellitus and chronic kidney failure. Delusional parasitosis is a primary psychiatric disorder in which affected patients have fixed, false beliefs that their skin is infested by parasites, in the absence of any evidence supporting their statements.